Sinergi Nilai Kearifan Lokal Banten dan Computational Thinking dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Yoma Hatima (FKIP UNSULTRA, 2025)
Learning Indonesian in elementary schools requires an approach that is not only cognitive but also contextual and adaptive to current developments. Banten's local wisdom, rich in noble values such as respect for nature, social solidarity, and ethical communication, offers significant potential for integration into learning. Furthermore, the computational thinking (CT) approach, which emphasizes logical, analytical, and problem-solving skills, is increasingly relevant in 21st-century education. This literature study aims to explore the synergy between Banten's local wisdom values and CT principles in Indonesian language learning at the elementary school level. This research employed a qualitative approach based on literature review, reviewing various articles, journals, books, and recent educational documents. The study's findings indicate that the synergy between local values and CT can improve literacy skills and critical thinking skills, as well as foster adaptive student character while remaining rooted in local culture. Local wisdom values can be used as context for CT assignments such as narrative algorithms and the decomposition of regional story texts. This study recommends the systematic integration of local culture into CT-based learning within the Indonesian language curriculum and learning strategies.